2011
DOI: 10.3892/mmr.2011.487
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extracts of black pepper or turmeric down-regulated SIRT1 protein expression in Daudi culture cells

Abstract: Abstract. SIRT1 is a mammalian candidate molecule involved in longevity and diverse metabolic processes. The present study aimed to determine the effects of certain herbs and spices on SIRT1 expression. Human cell lines Daudi, Jurkat, U937 and K562 were cultured in RPMI-1640. Herb and spice powders were prepared and the supernatants were collected. RT-PCR was used to quantify the expression level of the gene. Protein samples were then analyzed by Western blotting. Western blotting revealed the down-regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Due its medicinal properties, it is used in traditional medicine for its antioxidant, anti-inflammatory and anticancer properties [2,3]. This species is the second most widely traded spice in the world, accounting for a value of 929 million US dollars from a production of 445900 tons in 2009 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Due its medicinal properties, it is used in traditional medicine for its antioxidant, anti-inflammatory and anticancer properties [2,3]. This species is the second most widely traded spice in the world, accounting for a value of 929 million US dollars from a production of 445900 tons in 2009 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Grabowska et al observed that curcumin elevates SIRT1 levels in human vascular cells (12), Sahin et al reported the elevation of SIRT1 and prevention of muscle damage by supplementation of novel watersoluble CW formulation in rats (20), and Ray Hamidie et al showed that Curcumin injection in combination with exercise training increased cytosol NAD+/NADH ratio and SIRT1 protein in Wistar rats muscles (19). But Nishimora et al reported the down regulation of SIRT1 expression with ethanol extract of turmeric in human cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…Black pepper (Piper nigrum L.) is the most traded spice in the world, widely used in cooking, food preservation and perfume production. Some black pepper chemicals also have medicinal properties, such as antioxidant, anti-inflammatory and anticancer activities (Liu et al 2010;Meghwal and Goswami 2013;Nishimura et al 2011). The global production of black pepper from tropical countries is about 334,000 tonnes, totaling 1.8 billion US dollars.…”
Section: Introductionmentioning
confidence: 99%